Bio-Inspired Sensory Systems - Brooks, Geoffrey (Open textbook library., 2021)
Using natural sensory system concepts to develop and improve sensory systems will continue to thrive for many years to come. Technology advances rapidly (Moore’s Law) as does our understanding of biological principles and designs. These trends fuel the fertile grounds of bio-inspired sensory systems, a topic that is inherently multidisciplinary. This book will serve well as either an academic text on the subject or an introduction to the variety of proven bio-inspired designs. The focus is on sensory systems that interpret environmental stimuli. It introduces natural photo-, mechano-, and chemo-sensory systems across the animal kingdom and also summarizes various novel engineering ideas that glean ideas from these natural sensory systems.